Introduction to the Special Issue: Select Papers Presented at Recent OLC Conferences - Moskal, Patsy; Carrie Lewis Miller; Dara Tafazoli (Online Learning, 2025)
Each year, the September issue of the Online Learning Journal (OLJ) highlights select articles showcasing research presented at one of the past year's Online Learning Consortium (OLC) conferences, OLC Accelerate or OLC Innovate. This special issue continues this tradition by presenting seven studies that demonstrate the breadth and depth of current scholarship in online and digital learning. The selected papers address critical areas including leadership competencies, mobile-assisted language learning, student success factors, instructional design effectiveness, faculty motivation and support, and innovative pedagogical approaches using generative artificial intelligence. These studies offer valuable insights into the evolving landscape of online education and provide evidence-based practices for educators, administrators, and researchers working to enhance the quality and effectiveness of digital learning environments